THE RELATIONSHIP OF PERSONALITY TYPE AND DEPRESSION IN ELDERLY - Setyoadi, Setyoadi; Chuluq Ar., A. Chusnul; Teguhwahyuni, Kristien (Jurnal Keperawatan, 2012)
Psychological health problems would arise if the elderly can not adapt properly to the changes following aging process, which is can be performed as depression. The adaptation ability of the elderly is affected by their personality type. The personality type would determine the elderly’s vulnerability to the depression. This study aimed to investigate the relationship of personality type and depression in elderly. The design was observational analytic study with cross sectional approach design. Subjects were 74 elderly, taken by total sampling technique. The result of prevalence ratio (PR) calculation showed that: 1) constructive personality type was not the risk factor of depression (PR = 0,17); 2) independent personality type was the risk factor of depression (PR = 5,13); 3) self-hate personality type was the risk factor of depression (PR = 6,25). Based on the result it is suggested to the aging institution to encourage the elderly’s participation in every activities programmed and to improve it’s variation so that it can provided the eldery wider chance of social interaction, supported them to stay active and productive, and improved their self confident.